Ontological methods and tools for semantic extension of the media WIKI technology - Rogushina, J.V.; Grishanova, I.J. (Проблеми програмування, 2020)
Practical aspects of ontological approach to organization of intelligent Wiki-based information resources (IR) are considered. We analyze the main features, capabilities and limitations of MediaWiki as a technological platform for development of the Web-based information resource and suggest main directions of its refinement. We propose an abstract model of MediaWiki architecture that formalizes relations between the main components of this software environment and analyze the ways of its semantic extensions based on ontological representation of domain knowledge. An original algorithm of semantic Wiki pages matching with domain ontology is developed. We propose an ontological model of IR that formalizes its knowledge base structure and explicitly performs main features of typical information objects (TIO) of this IR. Such TIOs depend on domain specifics and purposes of IR, therefore their development has to involve domain experts and knowledge engineers. Use of ontology corresponding to the set of Wiki pages (either with semantic markup or without it) provides new IR functions associated with semantic search and navigation. Other important aspect of intelligent Wiki resource development deals with adaptation of user interface to the specifics of IR: enabling various tools of navigation, visualization and content analysis by processing of TIO features enriches IR functionality, reduces access time to information and makes usage of IR more efficient. Developing additional MediaWiki functionality with new requests to the MediaWiki API using TIO templates, extends data analysis and integration capabilities, and offers different, user-focused, IR content views expands the possibilities of data integration and proposes various user-oriented representations of IR content. Wiki resource semantization allows the use knowledge acquired from such IR by external application, or example, by search engines for intelligent Web retrieval. Domain ontologies based on various subsets of the Wiki pages and generated by them thesauri can be used by various Semantic Web applications, both independently or in general technological chain for personified retrieval focused on individual users and their tasks. Approbation of this approach is demonstrated by MAIPS retrieval system. We consider the use semantic similarity of concepts represented by Wiki-pages of IR as an additional way of intelligent navigation between these pages. Such approach allows to group Wiki pages according to user interests by different aspects of their content and structure. Wiki ontologies are considered as the basis for estimation of semantic similarity between domain concepts pertinent to user task. Such elements of Wiki ontology as classes, property values of class instances and relations between them are used as parameters for the quantitative assessment of semantic similarity of Wiki pages. We propose to use local similarity and generate the sets of semantically similar concepts (SSC) that takes into account some subset of page properties and categories defined by user needs. Such sets of SSCs can be considered as user task thesauri for other applications. In addition, we propose to enrich the basic tools of MediaWiki used for access management to the IR content with specialized software code that performs content classification that take into consideration separate namespaces, categories, templates and semantic properties of TIO acquired from Wiki markup. We demonstrate the software implementation of proposed solutions by developing of portal version of the Great Ukrainian Encyclopedia (e-VUE) that contains heterogeneous multimedia content with complex structure. We analyze the specifics of e-VUE knowledge system and develop its formalized TIO representation based on Semantic Web technologies and ontological analysis. Ontological model of e-VUE and original methods of its processing used for this project extend the functionality of the portal in the area of search, navigation, integration and protection of content based on background domain knowledge. In addition, original user interface of e-VUE is developed with an allowance for Encyclopedia knowledge specifics, substantially differs from the standard Wiki, meets the requirements, goals and objectives of this IR and provides a lot of additional features. Рассмотрены практические аспекты онтологического подхода к организации интеллектуальных информационных ресурсов (ИР) на основе Wiki. Проанализированы основные функции, возможности и ограничения MediaWiki как технологической платформы для разработки Web-ориентированных ИР и предложены основные направления ее усовершенствования. Мы используем онтологический подход к управлению знаниями ИР и предлагаем оригинальные алгоритмы сопоставления Wiki-страниц и онтологии предметной области (ПрО). Онтологическая модель ИР формализует структуру его базы знаний и явным образом представляет основные свойства типичных информационных объектов (ТИО) этого ИР. Семантизация Wiki-ресурса позволяет использовать знания, извлеченные из ИР, для интеллектуального поиска в Web внешними поисковыми системами. Онтологии ПрО, построенные на основе различных наборов Wiki-страниц такого ИР, и тезаурусы задач, генерируемые по этим онтологиям, могут использоваться различными приложениями Semantic Web как самостоятельно, так и в составе технологического цепочки для персонифицированного поиска. Кроме того, мы предлагаем обогатить основные инструменты управления доступом MediaWiki к контенту Wiki-ресурса специализированным программным кодом, который выполняет классификацию этого контента с использованием отдельных пространств имен, категорий, шаблонов и семантических свойств TИO, извлеченных из Wiki-разметки. Мы демонстрируем программную реализацию предложенных решений на примере портальной версии Большой украинской энциклопедии (e-VUE), которая содержит гетерогенный мультимедийный контент со сложной структурой. Онтологическая модель e-VUE и методы ее обработки обеспечивают расширение функциональности портала в сфере поиска, навигации, интеграции данных и защиты информации на основе фоновых знаний ПрО. e-VUE имеет оригинальный пользовательский интерфейс, который существенно отличается от стандартного Wiki, соответствует требованиям, задачам и целям энциклопедического издания и предоставляет пользователям портала дополнительные функции. Розглянуто практичні аспекти онтологічного підходу до організації інтелектуальних інформаційних ресурсів (IР) на основі Wiki. Проаналізовано основні функції, можливості та обмеження MediaWiki як технологічної платформи для розробки Web-орієнтованих ІР та запропоновано основні напрямки її вдосконалення. Ми пропонуємо абстрактну модель архітектури MediaWiki, яка формалізує відношення між основними компонентами цього програмного середовища, та аналізуємо шляхи її семантичного розширення на основі онтологічного подання знань. Ми використовуємо онтологічний підхід до управління знаннями ІР та пропонуємо оригінальні алгоритми співставлення Wiki-сторінок та онтології предметної області (ПрО) . Онтологічна модель ІР формалізує структуру його бази знань і явно подає основні властивості типових інформаційних об'єктів (ТІО) цього ІР. Вдосконалення засобів навігації, візуалізації та аналізу контенту шляхом обробки TIO збагачує функціональність ІР. Розробка додаткового функціоналу MediaWiki за допомогою запитів до MediaWiki API, які використовують шаблони TIO, розширює можливості аналізу та інтеграції даних і пропонує орієнтоване на користувача подання контенту ІР. Семантизація Wiki-ресурсу дозволяє використовувати знання, що здобуваються з нього, іншими застосуваннями, наприклад, для інтелектуального пошуку у Web зовнішніми пошуковими системами. Ми пропонуємо використовувати семантичну подібність понять для інтелектуальної навігації між сторінками ІР. Wiki-онтології використовуються як основа для оцінки семантичної подібності між поняттями ПрО відповідно до задач користувача. Ми пропонуємо використовувати локальну подібність та генерувати набори семантично подібних понять (СПП), приймаючи до уваги тільки визначену користувачем підмножину їх властивостей та категорій відповідно до його інформаційних потреб. Ми демонструємо програмну реалізацію запропонованих рішень на прикладі розробки портальної версії Великої української енциклопедії (e-VUE), що містить гетерогенний мультимедійний контент зі складною структурою. Онтологічна модель e-VUE та методи її обробки, що використовуються для цього проекту, забезпечують розширення функціональності порталу в сфері пошуку, навігації, інтеграції даних та захисту інформації на основі фонових знань ПрО. Крім того, e-VUE має оригінальний користувацький інтерфейс, який суттєво відрізняється від стандартного Wiki, відповідає вимогам, задачам та цілям енциклопедичного видання і надає користувачам порталу додаткові функції.